Riwayat Pembelajaran Bahasa Inggris dan Kecemasan Bahasa Asing pada Siswa SMP (Sekolah Menengah Pertama) (English Learning History and Foreign Language Anxiety among Junior High School Students0 - Sepniwati, Lelly; Simson Supardi, Jeffry; Sapotra, Ardo (Program Studi Psikologi Islam (IAIN) Kediri, 2025)
In Indonesia, many state junior high school students still have difficulty understanding English learning at school, even though they have been exposed to English on a varying scale. One of the psychological barriers that influences foreign language proficiency is foreign language anxiety. Therefore, this research seeks to investigate the level of foreign language anxiety experienced by state junior high school students in Bukit Batu District influenced by the history of English learning and the causal factors. The research methods used in this study are quantitative, using foreign language classroom anxiety scale instrument with 245 samples, and qualitative research using interview with 15 subjects. The research results show that students' level of English language anxiety is relatively high. When related to the history of learning English, students who have taken English courses have lower levels of English language anxiety because of the learning methods and learning facilities in the tutoring institution. Therefore, teachers and schools need to facilitate students by implementing more practical methods, using games as a learning medium, and establishing English afterschool activity so that students are more accustomed, comfortable, and enthusiastic about using English at school.